VD_FINDINFO HC / 2010 / 450 vom 28. Juni 2010 - VD Tribunal cantonal (2010)
DROIT DU TRAVAIL, RÉSILIATION IMMÉDIATE, JUSTE MOTIF, CONTRAT DE TRAVAIL, DÉLAI | 337 al. 1 CO, 337 al. 2 CO, 337 CO, 452 al. 1ter CPC, 452 al. 2 CPC, 452 CPC, 46 al. 1 LJT, 46 al. 2 LJT, 46 LJT